Sustainable Fertilization of Organic Sweet Cherry to Improve Physiology, Quality, Yield, and Soil Properties - Liliana Gaeta; Luigi Tarricone; Alessandro Persiani; Angelo Fiore; Francesco Montemurro; Daniela De Benedetto; Carolina Vitti; Pasquale Campi; Mariangela Diacono (Agronomy)
Sustainable fertilization techniques are essential in Mediterranean farming systems, where the depletion of organic matter, influencing soil water and nutrient availability, is becoming an increasing concern. In this context, organic fertilizers offer an effective strategy to restore soil fertility while reducing environmental impacts. This research aimed to evaluate the effects of different organic fertilizers on soil quality and tree performance in a sweet cherry (Prunus avium L.) orchard. This study was conducted in two growing seasons (2021–2022) in an organic orchard in Southern Italy, comparing four treatments: (i) compost, (ii) compost combined with compost tea, (iii) mixed manure, and (iv) an unfertilized control. The results indicated that compost tea, applied both to the soil and as a foliar spray, significantly improved tree water status, particularly under water stress conditions, as reflected by more negative stem water potential values. Moreover, this treatment enhanced photosynthetic performance, yield, and fruit quality, achieving the highest ratio of soluble solids content/total acidity. The findings suggest that compost tea, in combination with compost, could be a sustainable and valuable fertilization option for Mediterranean organic tree orchards. However, further studies are necessary to understand the benefits of other fruit orchards as well as the long-term effects on soils.